Modelling of stress transfer in fibre composites - Guild, F.J.; Vlattas, C.; Galiotis, C.
The finite element analysis method has been used to investigate stress transfer to a single Kevlar fibre embedded in epoxy resin. Results from the simulations have been compared with experimental results from the technique of Raman spectroscopy; this technique leads to direct measurement of fibre strain. The measured strain profiles can be converted to profiles of interracial shear stress. The predicted profiles of fibre strain and interracial shear stress are directly comparable to the experimental values; the accuracy of the method of conversion used for the experimental results can be assessed. The predictive model includes elasto-plastic behaviour of the resin; this behaviour is shown to have a critical effect on the transfer of strain to the fibre.
Keywords: FINITE ELEMENT ANALYSIS; RAMAN SPECTROSCOPY; STRESS TRANSFER; MICROMECHANICS; INTERRACIAL SHEAR STRESS